Analysis of smile photos posted on social networks as an alternative for human identification - Warney Pires FERREIRA; Vinícius Aguiar LAGES; Raimundo Rosendo PRADO JÚNIOR (Faculdade São Leopoldo Mandic, 2023)
ABSTRACT Photos of smiles posted on social media contain information on individuals' anatomical and oral morphological characteristics, which can be important for ante and post-mortem human identification, during confrontation for forensic purposes. Objective: The study aimed to evaluate the feasibility of using smile photographs on social networks as a source of information for human forensic identification. Methods: The study sample consisted of forty individuals, randomly divided into four equal groups, two groups in Instagram (IG®) and two groups in Facebook (FB®). Standardized oral photographs of the anterior teeth of the participants, from three different angles (post-mortem photos) were taken using a Nikon® EOS 550D camera. Photos of smiles posted in FB and IG by the participants were also collected (ante-mortem photos). The analysis were carried out by 4 forensic experts, 18 dental professors, and 21 dental students. They compared simulated ante and post-mortem photos, to identify the alleged victims. Results: The correct identification score ranged from 28.6% (students) to 100% (forensic experts). The most frequently reported dental characteristics used for the identification were morphology of the anterior teeth, zenith, and gingival recessions. There was no statistically significant association between the rate of correct identification and the degree of difficulty reported during the analysis (p= 0,068), whereas there was also no association between this index and or the duration of the analysis (p=0,884). Conclusions: Therefore, the photographs of the smile posted on social media proved to be a database of dental information, and with potential to assist in identification with dental forensic purposes.